The high molecular weight dipeptidyl peptidase IV Pol d 3 is a major allergen of Polistes dominula venom - Schiener, Maximilian (Sci Rep, 2018)
Hymenoptera venom allergy can cause severe anaphylaxis in untreated patients. Polistes dominula is an important elicitor of venom allergy in Southern Europe as well as in the United States. Due to its increased spreading to more moderate climate zones, Polistes venom allergy is likely to gain importance also in these areas. So far, only few allergens of Polistes dominula venom were identified as basis for component-resolved diagnostics. Therefore, this study aimed to broaden the available panel of important Polistes venom allergens. The 100 kDa allergen Pol d 3 was identified by mass spectrometry and found to be a dipeptidyl peptidase IV. Recombinantly produced Pol d 3 exhibited sIgE-reactivity with approximately 66% of Polistes venom-sensitized patients. Moreover, its clinical relevance was supported by the potent activation of basophils from allergic patients. Cross-reactivity with the dipeptidyl peptidases IV from honeybee and yellow jacket venom suggests the presence of exclusive as well as conserved IgE epitopes. The obtained data suggest a pivotal role of Pol d 3 as sensitizing component of Polistes venom, thus supporting its status as a major allergen of clinical relevance. Therefore, Pol d 3 might become a key element for proper diagnosis of Polistes venom allergy.